Meningitis and Bacteremia by Unusual Serotype of Salmonella enterica Strain: A Whole Genome Analysis - Thamer Brek; Gassem A. Gohal; Muhammad Yasir; Esam I. Azhar; Ibrahim A. Al-Zahrani (Interdisciplinary Perspectives on Infectious Diseases)
Background. Although meningitis caused by Salmonella species is relatively rare and accounts for <1% of the confirmed cases in neonates, it is associated with case complications and fatality rates up to 50–70% when compared to other forms of Gram-negative bacilli meningitis. Objectives. We conducted an investigation into the first reported case of neonatal meningitis caused by nontyphoidal S. enterica in Jazan, a region in the southwestern part of Saudi Arabia. Methods. CSF and blood culture were collected from a female neonate patient to confirm the presence of bacterial meningitis. WGS was conducted to find out the comprehensive genomic characterization of S. enterica isolate. Results. A 3-week-old infant was admitted to a local hospital with fever, poor feeding, and hypoactivity. She was diagnosed with Salmonella meningitis and bacteremia caused by S. enterica, which was sensitive to all antimicrobials tested. WGS revealed the specific strain to be S. enterica serotype Johannesburg JZ01, belonging to ST515 and cgMLST 304742. Conclusions. We presented a genomic report of rare case of NTS meningitis in an infant who is living in a rural town in Jazan region, Saudi Arabia. Further research is required to understand the impact of host genetic factors on invasive nontyphoidal Salmonella infection.